(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The article presents the results of the research aimed at determining the fluctuation of books and reading among seniors. It consists of two parts: the first – theoretical, introducing the issues of old age and reading, and the second – based on empirical research, regarding the reading behaviour of older people. The research was conducted at the turn of May and June 2022. A diagnostic survey method was used with the addition of the survey technique. The results of the research showed that reading books was an important component of seniors’ range of activities, and the vast majority of them declared that they read books. Reading books is the domain of women. The people who read most intensively were: women, respondents with the higher education, younger people and those living in larger cities. Seniors definitely prefer paper books. E-books and audiobooks attracted little interest. These preferences influence the collection of resources in home libraries. Having books at home was almost universal among the study group. Mainly traditional books were collected, e-books and audiobooks enjoyed minimal interest. ¾ of the respondents declared that they do not read e-books entirely. Those who do this most often use a computer screen. When it comes to the ways of obtaining paper books to read, the seniors surveyed primarily bought them, and e-books most often were received by them in the form of a file or link from a family member or a friend. The reading preferences of the surveyed seniors depended on individual needs and expectations, but older people were most willing to attain literature, which they treated as a form of pleasant spending of leisure time. It was mainly contemporary fiction, romances, biographical and historical books, crime and thriller literature. It was noticed that poetry attracted little interest. Based on the analysis of the National Library’s readership research and analyst’s own research, it was found that the rankings of the most read authors are dynamic lists that change from year to year.